Cellular Fatty Acids of Pathogenic Neisseria - Moss, C. Wayne (1970)
The cellular fatty acid composition of 20 isolates of Neisseria gonorrhoeae and 21 isolates of N. meningitidis was examined by gas-liquid chromatography. Each isolate of the two species possessed similar fatty acid profiles which were characterized by five major acids, accounting for 80 to 85% of the total. The three most abundant acids in each species were palmitic, palmitoleic, and β-hydroxylauric acids; lauric and myristic acids were the next most abundant. The presence of large amounts of β-hydroxylauric acid (20% or greater) and the relative concentrations of the other four major acids appear to be useful markers for distinguishing N. gonorrhoeae and N. meningitidis fatty acids from those of other bacteria.